2013
DOI: 10.1111/ajph.12033
|View full text |Cite
|
Sign up to set email alerts
|

New Nationalism in Australia and New Zealand: The Construction of National Identities by Two Labo(u)r Governments in the Early 1970s

Abstract: During the 1970s the Whitlam government in Australia and the Kirk government in New Zealand each adopted a policy of new nationalism in an attempt to come to terms with a rapidly changing and increasingly decolonised world marked by the decline of Britain as an economic and military force in the world. In each case this new nationalism prioritised local and national identities over a larger pan‐British identity. Both governments were more inward‐looking and yet also more engaged with the Asia‐Pacific region th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…27 In New Zealand, debate over the role has been less concerned with political affiliation and more concerned with the identity (ethnic or otherwise) of the individual called to the office. 28 The office of Governor General may therefore be understood as a distinctly Australian multi-faceted institution. 29 First, it is expected that the Governor General will behave in a way that is in tune with the Australian monarchy, yet due to the appointment process, they cannot claim to have as apolitical a role as that of the royal family.…”
Section: The Australian Governor Generalmentioning
confidence: 99%
“…27 In New Zealand, debate over the role has been less concerned with political affiliation and more concerned with the identity (ethnic or otherwise) of the individual called to the office. 28 The office of Governor General may therefore be understood as a distinctly Australian multi-faceted institution. 29 First, it is expected that the Governor General will behave in a way that is in tune with the Australian monarchy, yet due to the appointment process, they cannot claim to have as apolitical a role as that of the royal family.…”
Section: The Australian Governor Generalmentioning
confidence: 99%
“…In their study from the 1960s, Alex Mitchell and Arthur Delbridge (1965) identified three main varieties of Australian accent: ‘Broad’, ‘General’ and ‘Cultivated’. During the 1970s, when Prisoner first aired, this ‘Cultivated’ accent still endured despite being in sharp decline partly due to the new nationalism of the period, which was actively promoted by government and emphasised cultural self-definition and newfound appreciation of Australian English and the Australian accent (see Cao, 2012: 243; Doig, 2013). Before this, Australian film and broadcast media were heavily dominated by imported content from Britain and America, reflecting broader, cultural subservience to both these Anglo empires (see Cao, 2012; Cunningham, 1989).…”
Section: Prisoner Speakmentioning
confidence: 99%
“…The way in which Prisoner navigates between accent varieties serves to highlight Australian voice in all its complexity and nuance, while also dramatising and leveraging progressive 1970s cultural shifts towards the national vernacular (see Doig, 2013), imbuing its vocal register with added layers of cultural irreverence and anti-authoritarianism as was also at play in the era’s embrace of ‘Ocker’ types and tones (see Crofts, 1996; Dwyer, 2018a: 120–124; O’Regan, 1995). Prisoner ’s marked investment in vocal contrast highlighted and celebrated Australian voice and accent, provoking much comment and contributing to controversy caused by its salacious themes.…”
Section: Prisoner Speakmentioning
confidence: 99%
“…20 The nationalism he presented was less connected to the concerns of British Empire or the United Kingdom and more with an appeal to a domestic Australianness. 21 This approach was reinforced by pointing to the significant strategic change taking place with the continuing war in Vietnam and the retreat of the United Kingdom from Asia. While many of his senior colleagues were less willing to follow Gorton's line, he, on the whole, succeeded in pursuing this course by being re-elected in the general election in October 1969.…”
mentioning
confidence: 99%